Язык эмоций как интегративный формат репрезентации знаний - Шамаева, Ю.Ю.; Shamayeva, Yu.Yu. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2014)
Данная статья посвящена осмыслению языка эмоций как интегративной онтологии репрезентации знаний в языке с учетом его интерпретирующей функции. Особое внимание уделяется взаимодействию репрезентативного, семиотического и интерпретационного измерений оперирования знанием посредством языка эмоций как результата реализации ним базовых когнитивной, коммуникативной и интерпретирующей функций. Стаття присвячена осмисленню мови емоцій як інтегративної онтології репрезентації знань у мові з урахуванням її інтерпретуючої функції. Особлива увага приділяється взаємодії репрезентативного, семіотичного та інтерпретаційного вимірів оперування знаннями через мову емоцій як результата реалізації нею базових когнітивної, комунікативної та інтерпретуючої функції. The present article focuses on analyzing the language of emotions as an integrative ontology of representing knowledge in a language, taking into account its interpreting function. A special emphasis is on the interaction of the representative, semiotic and interpretative dimensions of operating knowledge through the language of emotions as the result of its realizing the core cognitive, communicative and interpretative functions.
The language of emotions as an integrative format of representing knowledge
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics; знание; интерпретация; репрезентация; эмоция; языковая функция; emotion; knowledge; interpretation; language function; representation